Разработка методов лечения послеродового эндометрита коров - Никогосян, Эрик; Варданян, Альберт; Григорян, Лиана; Мелконян, Жанна (ՀԱԱՀ հիմնադրամ)
Цель исследований – разработка наиболее эффективного метода лечения послеродового эндометрита у коров путем совместного применения антибактериальных препаратов широкого спектра действия, иммуностимулирующих и гормональных средств. Выявление эндометрита осуществляли клиническими, вагинальными и ректальными исследованиями животных. До начала и в течение лечения был проведен анализ гематологических и биохимических показателей крови, лейкопрофиля больных животных. Изучалась динамика течения заболевания в его процессе. Микробиологическими исследованиями изучен видовой состав патогенной микрофлоры вагинальных истечений подопытных коров и определена чувствительность патогенных микроорганизмов к разным антибиотикам. Нами был предложен новый метод с использованием Лексофлона, Метрикура, АСД фракции 2, Окситоцина и Синэстрола. Применение вышеуказанных препаратов позволило сократить длительность лечения послеродового эндометрита на 2-3 дня. The main objective of our research was to develop the most effective method for treating postpartum endometritis in cows using a combination of broad-spectrum antibacterial drugs, immunostimulants and hormonal agents. In order to detect endometritis, clinical, vaginal and rectal examinations of animals were conducted. Studies of hematological and biochemical blood parameters, leukoprofile parameters and the clinical picture of animals with postpartum endometritis were also conducted before and during treatment. Microbiological studies were used to study the species composition of pathogenic microflora of vaginal discharges of animals with endometritis and to determine the sensitivity of pathogenic microorganisms to various antibiotics. According to the principle of analogs, two groups of animals (control and experimental) were created, with 11 animals in each, which were kept in the same feeding and maintenance conditions. The control group of animals was treated upon daily uterine lavage with a sodium chloride solution, intrauterine administration of furazolidone suspension, and the antibiotic nitox intramuscularly. The experimental group was administered a broad-spectrum of antibiotic: lexoflon, as an antibacterial agent, intramuscularly, the drug metricur, as an antibacterial drug, intrauterinely, ASD fraction 2 was used as an immunostimulants, orally. For stimulating the contractile function of the uterus and to remove exudate, oxytocin was prescribed intramuscularly, and solution of sinestrol was used as an estrogen agent to increase the sensitivity of the uterus to oxytocin. The results of the studies indicate that the use of the above-mentioned drugs in experimental group made it possible to regulate hematological, blood biochemical, blood leykoprofile parametrs, and general condition of animals on 7-8th day of treatment enabling to reduce the duration of treatment for postpartum endometritis by 2-3 days.
Keywords: Ветеринарная медицина